Dialect lexicography for the southern Dutch dialects - Van Keymeulen, J (2010)
The paper will present an outline of the state of the art for dialect lexicography in the southern Dutch language area (i.e. Dutch-speaking Belgium and the three southern provinces of the Netherlands: Zeeland, North Brabant, Limburg). After a short discussion of what is Flemish, Zeelandic, Brabantic and Limburgian, I will dwell on the question why dialect vocabulary (i.e. the geographically differentiated vocabulary of the traditional dialects) has become an historical vocabulary. Next, the four regional dictionaries of the southern Dutch dialects will be presented: i.e. the alphabetically arranged Dictionary of the Zeeland Dialects (1964), and the three systematically arranged dictionaries for the Brabantic (1961-2005), Limburgian (1962-2008) and Flemish (1972 -) dialects. The general set-up and most important results of the three dictionaries will be discussed. It will be pointed out that the organisation of the three dictionaries (as advocated by the initiator, prof. A. Weijnen, of the Nijmegen University) has led to databases for word atlasses, rather than to dictionaries proper. Due to the fact that all lexical data in the four dictionaries are geographically documented in great detail, a word atlas is indeed possible on the basis of the combined databases of the three thematic dictionaries (with the Zeeland material added). For semantic detail, we have to call in the help of ʻamateurʼ dialect lexicography. Thanks to the rising interest in the disappearing dialect lexicon, a huge local dictionary production has emerged. A pilot project was launched in 2009, which envisaged the creation of a database for the regional / local dialect amateur dictionaries. In this way, both the geographical and semantic dimension of the dialect lexicon will be accounted for for future lexicological research.